Ni-Fe-based superalloy laser melting deposition formability control method and deposition layer preparation

By designing orthogonal test tables and optimizing process parameters in laser melt deposition Ni-Fe-based high-temperature alloys, and adding trace amounts of Y2O3 to the powder, the problems of process parameter optimization and thermal crack suppression in laser melt deposition are solved, and the mechanical properties of the deposition layer are significantly improved.

CN116275092BActive Publication Date: 2025-06-03SHANGHAI JIAOTONG UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211652118.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2025-06-03
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

During the laser melt deposition of Ni-Fe-based high-temperature alloys, it is difficult to efficiently obtain appropriate process parameters and reduce thermal cracks, resulting in insufficient strength and toughness of the deposited layer.

Method used

By designing an orthogonal test table for laser melting and deposition process conditions, the process parameters of single-channel and single-layer and multi-channel are optimized, and trace amounts of Y2O3 are added to the powder, and evenly mix them through the ball milling process to suppress the occurrence of thermal cracks.

Benefits of technology

It is realized that the appropriate process parameters are efficiently obtained during the laser melt deposition of Ni-Fe-based high-temperature alloys, reducing thermal cracks, and significantly improving the mechanical properties and plastic deformation resistance of the deposited layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116275092B_ABST
    Figure CN116275092B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for regulating the formability of a Ni-Fe-based superalloy by laser melting deposition and a method for preparing a deposited layer. The preparation method includes: evaluating the geometric morphologies of single-layer single-pass, single-layer multi-pass, and multi-layer multi-pass to determine the process conditions of laser melting deposition; incorporating Y2O3 into the Ni-Fe-based alloy powder and performing laser melting deposition to obtain a Ni-Fe-based superalloy laser melting deposited layer. Compared with the prior art, the present invention not only forms a deposited layer with good surface morphology, high density, and no cracks, but also evenly mixes Y2O3 with the Ni-Fe-based superalloy powder by using a ball milling process. By utilizing the role of Y2O3 in purifying the microstructure and refining the grains, the anti-plastic deformation ability of the Ni-Fe-based superalloy deposited layer is enhanced, thereby improving the comprehensive mechanical properties of the deposited layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of laser melting deposition of Ni-Fe based superalloys, and relates to a method for regulating the shape and properties of laser melting deposition of Ni-Fe based superalloys and a method for preparing a deposited layer. Background Art

[0002] The laser melting deposition technology uses a high-power laser beam as a heat source, and combines a special powder nozzle to co-axially deliver the powder and the laser, and gradually stacks the materials layer by layer on the substrate to realize the direct manufacturing of parts, which can meet the remanufacturing and repair requirements of some parts with complex structures and high-precision and high-bonding strength requirements. The laser melting deposition process is complex, and the factors affecting its forming quality include laser characteristics, material characteristics, forming process, environmental conditions, etc. Therefore, how to efficiently obtain appropriate process parameters for laser melting deposition to manufacture high-performance parts is a difficult challenge. At the same time, deposition layer defects are another major problem faced by laser melting deposition of Ni-Fe based superalloys. Common laser melting deposition defects include pores, cracks, inclusions, etc., especially the thermal cracks during the deposition process, which have a fatal impact on the performance of the deposited layer. In summary, it is of great significance to efficiently obtain appropriate process parameters and reduce cracks to improve the strength and toughness of the deposited layer.

[0003] In the optimization of laser melting deposition process parameters, in the patent application with the application publication number CN107217256A, orthogonal experiments are carried out by changing the laser power, scanning speed, powder feeding rate and shielding gas flow rate. Although the optimal process parameters of a single-pass deposited layer are obtained by this method, in actual parts, they are formed by multi-pass layering and multi-layer blocking. The morphology of each layer during the process will affect the forming quality and performance of the next layer. The inter-pass offset and the inter-layer offset are both important factors that need to be considered. At the same time, in order to improve the mechanical properties of Ni-Fe based superalloys, in the patent application with the application publication number CN112008079A, the formed layer is scanned twice by using a low-power laser and a slow scanning speed. This method realizes the control of cracks during the laser additive process of nickel-based superalloys, but makes the process steps complicated and increases the production cost in actual applications.

[0004] Therefore, on the premise of obtaining the optimal process parameters through orthogonal experiments, it is necessary to consider the interaction between passes and between layers, and evaluate the forming performance of parts with appropriate evaluation indicators. At the same time, select appropriate control means to suppress the thermal cracks during the laser melting deposition of Ni-Fe based superalloys and prepare formed parts with excellent mechanical properties. Summary of the Invention

[0005] The object of the present invention is to provide a method for regulating the shape and properties of Ni-Fe based superalloy by laser melting deposition and a method for preparing a deposited layer, so as to efficiently obtain appropriate process parameters for melting deposition to manufacture high-performance parts, and adding trace amounts of Y 2 O 3 to inhibit thermal cracks in multi-layer and multi-pass deposition of Ni-Fe based superalloys, and finally prepare components with excellent mechanical properties through laser melting deposition technology.

[0006] The object of the present invention can be achieved by the following technical solutions:

[0007] A method for regulating the shape and properties of Ni-Fe based superalloy by laser melting deposition, as Figure 1 shown, includes:

[0008] S1: Design an orthogonal test table for laser melting deposition process conditions, conduct single-pass and single-layer Ni-Fe based superalloy laser melting deposition tests, and determine the laser melting deposition process conditions based on the evaluation of the geometric morphology of the deposited layer;

[0009] S2: Set different inter-pass offsets, conduct single-layer and multi-pass laser melting deposition tests, evaluate the forming quality of single-layer and multi-pass with valley-peak distance, and determine the inter-pass offset;

[0010] S3: Add different proportions of Y 2 O 3 , obtain the influence of Y 2 O 3 on laser melting forming, and select the optimal Y 2 O 3 content;

[0011] S4. Use the layer height obtained under the optimal process parameters in step S1 as the inter-layer offset, conduct multi-layer and multi-pass laser melting deposition with and without Y 2 O 3 addition, compare the mechanical properties of the two, and obtain the Ni-Fe based laser cladding layer after shape and property regulation.

[0012] Furthermore, the doping amount of the Y 2 O 3 is 0.25 - 1.0 wt% of the Ni-Fe based alloy powder.

[0013] Furthermore, the Ni-Fe based alloy powder includes components and weight content:

[0014] Ni: 36 - 38 parts, Fe: 5 parts, Co: 20 parts, Cr: 25 parts, W: 8 - 9 parts, Al: 3 parts, Ti: 0.5 part, C: 0.8 - 0.9 parts.

[0015] Furthermore, Y 2 O3 Add Ni-Fe based alloy powder, where the ball milling speed is 300 r / min, the ball milling time is 2 - 3 h, and the ball-to-powder ratio is 2:1. Before the experiment, the ball-milled composite powder is placed in a drying oven and dried at a constant temperature of 120 °C for 3 h.

[0016] Further, step S1 includes: designing an orthogonal test table, and processing and analyzing the test results using intuitive analysis, variance analysis, and significance analysis methods. With the wetting angle 30° < θ < 60° and the dilution rate of 30% - 50% as the evaluation indexes for the formability of the deposition layer, select appropriate laser power, scanning speed, and powder feeding speed;

[0017] Step S2 includes: setting different inter-pass offsets, and continuously forming 3 - 7 passes at each inter-pass offset. The quality of single-layer multi-pass forming is evaluated by the valley-peak distance, that is, the smaller the valley-peak distance, the better the forming quality;

[0018] Among them, the calculation method of the valley-peak distance is as follows: Define the lowest point where two adjacent passes are connected as the "valley", draw a horizontal line segment tangent to the arc of the two deposition layers, and define this tangent line as the "peak line". The shortest distance from the "valley" to the "peak line" is the valley-peak distance.

[0019] Further, the laser melting deposition process includes cladding the powder on the substrate by a cross-scanning method under the protection of inert gas through a laser cladding device.

[0020] Further, during the laser melting deposition process, the laser spot diameter is 1.0 - 1.2 mm, the laser power is 800 - 900 W, the scanning speed is 12 - 14 mm / s, the scanning spacing is 0.8 - 0.9 mm, the layer spacing is 0.3 - 0.5 mm, the powder feeding speed is 0.4 - 0.5 r / min, and the powder feeding gas flow rate is 8 - 12 L / min.

[0021] A preparation method for a laser melting deposition layer of Ni-Fe based superalloy, including: adding Y 2 O 3 to the Ni-Fe based alloy powder and performing laser melting deposition, then a laser melting deposition layer of Ni-Fe based superalloy is obtained.

[0022] Further, the doping amount of the Y 2 O 3 is 0.25 - 1.0 wt% of the Ni-Fe based alloy powder; the Ni-Fe based alloy powder includes the following components and weight fraction contents: Ni: 36 - 38 parts, Fe: 5 parts, Co: 20 parts, Cr: 25 parts, W: 8 - 9 parts, Al: 3 parts, Ti: 0.5 part, C: 0.8 - 0.9 parts;

[0023] The particle size range of the Ni-Fe based superalloy powder described is 50 - 150 μm, and the particle size of the Y 2 O 3 powder is 50 - 100 nm;

[0024] During the laser melting deposition process, the laser spot diameter is 1.0 - 1.2 mm, the laser power is 800 - 900 W, the scanning speed is 12 - 14 mm / s, the scanning spacing is 0.8 - 0.9 mm, the layer spacing is 0.3 - 0.5 mm, the powder feeding speed is 0.4 - 0.5 r / min, and the powder feeding gas flow rate is 8 - 12 L / min.

[0025] Compared with the prior art, the present invention has the following characteristics:

[0026] The present invention uses orthogonal experiments to efficiently obtain appropriate process parameters for single-layer single-pass laser melting deposition, then selects an appropriate channel spacing for single-layer multi-pass deposition to form a deposition layer with good surface morphology, and optimizes the forming performance throughout the entire process of laser melting deposition of Ni-Fe based superalloy. At the same time, the ball milling process is used to uniformly mix Y 2 O 3 with the Ni-Fe based superalloy powder. Utilizing the function of Y 2 O 3 to purify the structure and refine the grains, the anti-plastic deformation ability of the Ni-Fe based superalloy deposition layer is enhanced, thereby improving the comprehensive mechanical properties of the deposition layer. Description of the Drawings

[0027] Figure 1 It is a flow chart of a method for regulating the forming properties of laser melting deposition of a Ni-Fe based superalloy in an embodiment.

[0028] Figure 2 It is a schematic cross-sectional view of a single-pass deposition layer of laser melting deposition of Ni-Fe based superalloy;

[0029] Figure 3 It is an effect curve graph of the influence of different process parameters of laser melting deposition on the formability;

[0030] Figure 4 It is a schematic diagram (upper) of the measurement method of the valley-peak distance of a single-layer multi-pass deposition layer of laser melting deposition and a graph (lower) of the change trend of the valley-peak distance with the channel offset;

[0031] Figure 5 It is a graph of the change trend of the geometric characteristic parameters of laser melting deposition of Ni-Fe based superalloy with the Y 2 O 3 content;

[0032] Figure 6a It is a schematic diagram of the overall morphology of a multi-layer multi-pass deposition layer of laser melting deposition of Ni-Fe based superalloy;

[0033] Figure 6b For laser melting deposition of 0.5 wt.% Y 2 O 3 / Ni-Fe-based superalloy multi-layer and multi-pass deposition layer overall morphology diagram;

[0034] Figure 7 For the tensile stress-strain curve diagram of Ni-Fe-based superalloy by laser melting deposition;

[0035] Figure 8 For the grain size distribution diagram of Ni-Fe-based superalloy by laser melting deposition. Specific implementation manners

[0036] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments. This embodiment is implemented on the premise of the technical solution of the present invention, and gives detailed implementation manners and specific operation processes, but the protection scope of the present invention is not limited to the following embodiments.

[0037] Embodiment:

[0038] Such as Figure 1 shown, a method for regulating the shape and properties of Ni-Fe-based superalloy by laser melting deposition includes:

[0039] S1: Optimization of the process conditions for single-pass and single-layer Ni-Fe-based superalloy laser melting deposition:

[0040] S1-1: The deposited powder is a FeNiCoCr superalloy (Ni: 37.7 parts, Fe: 5 parts, Co: 20 parts, Cr: 25 parts, W: 8 parts, Al: 3 parts, Ti: 0.5 parts, C: 0.8 parts, particle size range is 50 - 150 μm). This powder is deposited on the substrate by a laser cladding device in a cross-cross scanning manner under the protection of an inert gas to form a deposition layer; among them, the schematic diagram of the cross-section of the single-pass deposition layer formed by laser melting deposition is as Figure 2 shown. The geometric features that can reflect the morphology of the single-pass deposition layer are mainly the deposition layer height (H), deposition layer width (W), wetting angle (θ), melt depth (H f ), deposition layer area (S) and melt depth area (S f ). Among them, the most basic characteristic parameters are the height of the deposition layer, the width of the deposition layer and the wetting angle. The melt depth and melt depth area are usually combined with the layer height and deposition layer area to reflect the dilution degree of the substrate to the deposition layer, which is usually reflected by the dilution rate η. The specific calculation formula of the dilution rate can be simplified as:

[0041]

[0042] S1-2: In the laser melting deposition of this embodiment, the conventional parameters (the spot diameter of the laser focus is 1.2 mm, the diameter of the powder spot convergence is 2 mm, and the protective gas flow rate is 15 L / min) are all set to fixed values. Therefore, the laser power, scanning speed, and powder feeding speed have an impact on the geometric morphology of the single-pass deposition layer in laser melting deposition. In this embodiment, three process parameters, namely laser power, scanning speed, and powder feeding speed, are selected, and an L orthogonal experiment table with three factors, four levels, and two blank columns is designed. Only 16 groups of experiments need to be completed to comprehensively analyze the influence of the three process parameters on the geometric morphology of the single-pass deposition layer. The selected laser power range is 600 - 900 W, the scanning speed range is 8 - 14 mm / s, and the powder feeding speed range is 0.4 - 0.7 r / min. Each of the three factors is set with four levels. The geometric feature results of the 16 groups of process parameter sets and their corresponding combinations of the deposition layer are shown in Table 1. 16 (4 5 ) type orthogonal experiment table, and only 16 groups of experiments need to be completed to comprehensively analyze the influence of the three process parameters on the geometric morphology of the single-pass deposition layer. The selected laser power range is 600 - 900 W, the scanning speed range is 8 - 14 mm / s, and the powder feeding speed range is 0.4 - 0.7 r / min. Each of the three factors is set with four levels. The geometric feature results of the 16 groups of process parameter sets and their corresponding combinations of the deposition layer are shown in Table 1.

[0043] Table 1 Statistical table of 16 groups of orthogonal experiment process parameter sets and geometric characteristics of the deposition layer

[0044]

[0045] S1-3: Conduct intuitive analysis, variance analysis, and significance analysis. By calculating the average value of the four levels of each factor, the effect curves corresponding to the levels of laser power, scanning speed, and powder feeding speed are plotted. As shown in the figure, the preferred process conditions include a laser power of 800 - 900 W, a scanning speed of 12 - 14 mm / s, and a powder feeding speed of 0.4 - 0.5 r / min. Figure 3 As shown, the preferred process conditions include a laser power of 800 - 900 W, a scanning speed of 12 - 14 mm / s, and a powder feeding speed of 0.4 - 0.5 r / min.

[0046] Furthermore, preferably, under the process parameters of a laser power of 900 W, a scanning speed of 14 mm / s, and a powder feeding speed of 0.5 r / min, the deposition layer obtains the best geometric characteristic parameters: the deposition layer height is 469 μm, the deposition layer width is 1477 μm, the wetting angle is 50°, and the dilution rate is 35.4%.

[0047] S2: Optimization of the inter-pass offset in the single-layer multi-pass Ni-Fe-based superalloy laser melting deposition process:

[0048] S2-1: Conduct laser melting deposition of a single-layer multi-pass Ni-Fe-based superalloy. Under the optimal process parameters (laser power of 900 W, scanning speed of 14 mm / s, and powder feeding speed of 0.5 r / min) determined in step 1, the deposition layer width is 1477 μm. Generally, the inter-pass offset is set to a value less than the deposition layer width. Therefore, based on the above optimal parameters, the inter-pass offsets are set to 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, and 1.2 mm respectively. Five consecutive passes are formed at each inter-pass offset for single-layer deposition.

[0049] S2-2: Calculate the valley-peak distance at each inter-track offset. The calculation method of the valley-peak distance is as follows: Define the lowest point where two adjacent tracks are connected as the "valley". Draw a horizontal line segment tangent to the arc of the two deposited layers, and define this tangent line as the "peak line". The shortest distance from the "valley" to the "peak line" is the valley-peak distance. The schematic diagram of the valley-peak distance is shown in Figure 4 (upper). The variation trend of the valley-peak distance with the inter-track offset is as shown in Figure 4 (lower). It can be seen from Figure 4 that when the inter-track offset is 0.9 mm, the valley-peak distance of the single-layer deposited layer is the smallest, and the flatness of the upper surface of the deposited layer is the best. Therefore, the inter-track offset is finally selected as 0.9 mm.

[0050] S2-3: Calculate the inter-track overlap ratio at this inter-track offset. The calculation formula of the overlap ratio η o is as follows:

[0051]

[0052] where W represents the width of the deposited layer and D represents the inter-track offset. It can be calculated that when the inter-track offset is 0.8 - 0.9 mm, the inter-track overlap ratio is 35.6%. When the inter-track overlap ratio of laser additive manufacturing is about 30%, the formed part has good comprehensive performance, indicating that the selected process parameters are relatively reasonable.

[0053] Determination of the inter-layer offset in the multi-layer and multi-track laser melting deposition process of Ni-Fe-based superalloy:

[0054] Perform laser melting deposition of multi-layer and multi-track Ni-Fe-based superalloy. At the best inter-track offset of 0.9 mm obtained in step S2, the valley-peak distance of the single-layer deposited layer is the smallest. At this time, the height of the single-layer deposited layer (the shortest distance from the substrate to the upper surface of the deposited layer) is measured to be 0.37 mm. Take this layer height as the inter-layer offset, and finally form a rectangular sample of 20 mm × 10 mm × 5 mm, and use the Archimedes drainage method to test the density of the sample to evaluate whether the parameters are reasonable. The measured density of the sample is 98.9%, and the density of the sample is very close to 100%, indicating that the selected process parameters are relatively reasonable;

[0055] S3: Y 2 O 3 In the laser melting deposition process of Y 2 O 3 doped multi-layer and multi-track Ni-Fe-based superalloy, determination of the Y

[0056] The deposited powder is Y 2 O 3 / FeNiCoCr composite powder, Y 2 O 3With a diameter of 50 nm, Y 2 O 3 / Ni-Fe-based superalloy single-pass deposition layers with contents of 0 wt.%, 0.25 wt.%, 0.5 wt.%, 0.75 wt.%, and 1 wt.% of Y 2 O 3 were prepared, and a graph of the variation trend of the geometric characteristic parameters as shown in Figure 5 with respect to the Y 2 O 3 content was plotted. The wetting angle of the single-pass deposition layer is between 30% and 50%, and a wetting angle in the range of 30° to 60° is appropriate. The deposition layers with 0.25 wt.% and 0.5 wt.% Y 2 O 3 contents can meet these two conditions. By comparing the differences in the geometric characteristics of the deposition layers at these two contents, the deposition layers with 0.25 wt.% and 0.5 wt.% Y 2 O 3 contents have similar heights, but the width of the deposition layer with 0.5 wt.% Y 2 O 3 content is higher than that with 0.25 wt.% content. Considering the deposition efficiency in the horizontal and height directions of the composite powder, it can be determined that the content of 0.5 wt.% Y 2 O 3 is the optimal content for the experimental group.

[0057] S4: Multilayer and multi-pass deposition layers with and without Y 2 O 3 addition were formed respectively, and the overall morphology diagrams of the two deposition layers were observed, as shown in Figure 6a and 6b respectively. It can be found that compared with the deposition layer without Y 2 O 3 addition, no cracks were found in the deposition layer with 0.5 wt.% Y 2 O 3 content, and the overall molten pool is more uniform. This indicates that adding Y 2 O 3 can effectively eliminate liquefaction cracks during the laser melting deposition process and improve the microstructure and uniformity of the laser melted deposited Ni-Fe-based superalloy.

[0058] The Ni-Fe-based superalloy laser melted deposition formed parts strengthened by Y 2 O 3 were completed, and the subsequent room temperature tensile test was carried out to obtain the tensile curve as shown in Figure 7 . By comparing with the formed parts without Y 2 O 3 strengthening, adding Y 2 O 3The tensile strength of the formed part has increased from 970 MPa to 1148 MPa, with a 18.3% increase in tensile strength, while the elongation has increased from 5.9% to 14.5%, a 141% increase in elongation. Comparing the average grain sizes of the two, as Figure 8 shown, the average grain diameter has decreased from 50.12 μm to 38.12 μm. This grain refinement is caused by two factors: First, nano Y 2 O 3 can serve as heterogeneous nucleation sites, which can increase the number of heterogeneous nucleation. The more the number of crystal nuclei, the finer the finally formed grains. Second, due to the multi-layer and multi-pass forming process of laser melting deposition, multiple thermal cycles are experienced. The solidified metal will undergo dynamic recrystallization during this process, and nano Y 2 O 3 will produce a pinning effect during the crystallization process, thus hindering the migration of grain boundaries and achieving the effect of refining grains. The effect of refining grains effectively hinders the movement of dislocations and the propagation of cracks, greatly increasing the energy required for the failure of the composite material, thereby significantly improving the strength and toughness of the Ni-Fe-based superalloy formed part.

[0059] The above description of the embodiments is for the convenience of those of ordinary skill in the art to understand and use the invention. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative labor. Therefore, the present invention is not limited to the above embodiments, and the improvements and modifications made by those skilled in the art without departing from the scope of the present invention according to the disclosure of the present invention should be within the protection scope of the present invention.

Claims

1. A preparation method for a laser melting deposition layer of a Ni-Fe-based superalloy, characterized in that, it includes: Y 2 O 3 Adding into Ni-Fe based alloy powder and performing laser melting deposition, thus obtaining a Ni-Fe based laser cladding layer with regulated shape and properties; The described Y 2 O 3 has a doping amount of 0.5 wt% of the Ni-Fe based alloy powder; The Ni-Fe-based alloy powder described includes the following components and their weight contents: Ni: 36 - 38 parts, Fe: 5 parts, Co: 20 parts, Cr: 25 parts, W: 8 - 9 parts, Al: 3 parts, Ti: 0.5 part, C: 0.8 - 0.9 parts; The particle size range of the described Ni-Fe-based superalloy powder is 50 - 150 μm, and the particle size of the Y 2 O 3 powder is 50 - 100 nm.

2. The preparation method for a laser melting deposition layer of a Ni-Fe-based superalloy according to claim 1, characterized in that, this method further includes: S1: Design an orthogonal test table for laser melting deposition process conditions, conduct a single-pass and single-layer Ni-Fe-based superalloy laser melting deposition test, and determine the laser melting deposition process conditions based on the evaluation of the deposition layer geometric morphology; S2: Set different inter-pass offsets, conduct a single-layer and multi-pass laser melting deposition test, and evaluate the forming quality of the single-layer and multi-pass with the valley-peak distance, and determine the inter-pass offset; S3: Determine the inter-layer offset of the multi-layer and multi-pass Ni-Fe-based superalloy according to the layer height obtained under the laser melting deposition process conditions determined in step S1.

3. The preparation method for a laser melting deposition layer of a Ni-Fe-based superalloy according to claim 2, characterized in that, step S1 includes: Design an orthogonal test table, and use the methods of intuitive analysis, variance analysis, and significance analysis to process and analyze the test results. With the wetting angle 30° < θ < 60° and the dilution rate of 30% - 50% as the evaluation indicators for the deposition layer formability, select appropriate laser power, scanning speed, and powder feeding speed; step S2 includes: Set different inter-pass offsets, and continuously form 3 - 7 passes under each inter-pass offset, and evaluate the forming quality of the single-layer and multi-pass with the valley-peak distance, that is, the smaller the valley-peak distance, the better the forming quality.

4. The preparation method for a laser melting deposition layer of a Ni-Fe-based superalloy according to claim 1, characterized in that, the laser melting deposition process includes cladding the powder on the substrate in a cross-cross scanning manner by a laser cladding device under the protection of an inert gas.

5. The preparation method for a laser melting deposition layer of a Ni-Fe-based superalloy according to claim 1, characterized in that, during the laser melting deposition process, the laser spot diameter is 1.0 - 1.2 mm, the laser power is 800 - 900 W, the scanning speed is 12 - 14 mm / s, the scanning spacing is 0.8 - 0.9 mm, the layer spacing is 0.3 - 0.5 mm, the powder feeding speed is 0.4 - 0.5 r / min, and the powder feeding gas flow rate is 8 - 12 L / min.

6. The preparation method for a laser melting deposition layer of a Ni-Fe-based superalloy according to claim 1, characterized in that, during the laser melting deposition process, the laser spot diameter is 1.0 - 1.2 mm, the laser power is 800 - 900 W, the scanning speed is 12 - 14 mm / s, the scanning spacing is 0.8 - 0.9 mm, the layer spacing is 0.3 - 0.5 mm, the powder feeding speed is 0.4 - 0.5 r / min, and the powder feeding gas flow rate is 8 - 12 L / min.

Citation Information

Patent Citations

  • Laser cladding 316L stainless steel optimizing process

    CN107217256A

  • Method for improving mechanical property of 3D printing nickel-based superalloy through in-situ heat treatment

    CN112008079A

  • High-temperature-resistant oxidation coating nickel-based alloy powder for laser cladding

    CN110331397A

  • Metal alloy

    GB201700419D0